(untitled) (Rassegna di Diritto, Legislazione e Medicina Legale Veterinaria, 2017)
With the application of Legislative Decree no. 193/2007, Italy has partially solved the administrative problems about the application of the EU Regulations on food safety, even if the European provisions had to be directly applied from 1st January 2006. The European Commission was pursuing a legal action against Italy for failing to comply properly with their obligations under EU law. These decisions covering many sectors aim to ensure proper application of EU law for the benefit of citizens and businesses. For this reason the European Union was starting a proceeding for Italy for missing the application of the Directive 2004/41/EC, which repealed all the directives in conflict with the EU regulations, despite our legal system provides for the indirect repeal of laws in time. In particular, Authors analyze the issue related to the legal authorizations for food industries.